AGAMA DAN KEMANUSIAAN: IMPLEMENTASI AJARAN AGAMA TERHADAP AKSI SOSIAL - Abdul Qodir (Sadra International Institute, 2023)
Religion is not only defined as the relationship between the Creatorand His creations but can also function as a basis for social actionin the form of religious philanthropic movements and be appliedthrough various humanitarian activities. This paper aims toexplain that humanitarian social movements can be carried out byinstitutions initiated and based on religious principles. The purposeof these institutions is to distribute aid and strive to improve theliving standards of marginalized groups or the poor. In its concept,the welfare of the poor is not sufficient merely by providing economicassistance in the form of charity; it must be complemented withlong-term programs such as education, health, skills training, andprogram monitoring. Therefore, religious philanthropy has an activerole in providing universal public services without discriminationbetween individuals.